Endoscopic treatment of vesicoureteral reflux in a paediatric surgery ambulatory unit - Fernando Rivilla (Journal of Minimal Access Surgery, 2011)
Background: Vesicoureteral reflux (VUR) is a major urological problem in children. Its incidence ranges from 1 to 3% in healthy children. Materials and Methods: We treated 38 children and analysed their data on age, sex, reflux grade, laterality, and results of endoscopic treatment (ET), at the different grades of reflux. All children were operated on an Ambulatory Surgery basis, studying the complications and post-operative course. Results: Thirty-eight patients were operated during a period of six years, of age between one and twelve years. VUR was bilateral in 24 (63%) patients, unilateral in 14 (34%), with a collection of a total of 62 renal units or ureters. In 29 children (76%), 46 refluxing ureters (70%) completely disappeared after just 1 ET. Nine patients (24%) with 16 ureteral units (30%) received a second ET, with the reflux disappearing successfully in seven children (12 ureteral units), changing the success rate in the disappearance of VUR, after two injections of Deflux, to 90% of the total group of ureters (58 of 62). Conclusion: The endoscopic treatment of VUR has become the first choice of treatment to control the primary reflux, not just because of the good results, but because of the low post-operative morbidity and the direct relationship with the Ambulatory Surgery Unit.